Effects of nest locations on foraging behavior and physiological responses in seabird colony - Mizutani, Yuichi; Goto, Yusuke; Shoji, Akiko; Yoda, Ken (Frontiers in Physiology, 2025)
Breeding success and survival in colonial seabirds are influenced by nest location, physical surroundings, and external disturbances. Nest location may also directly or indirectly affect individual foraging behavior and physiological conditions, shaping reproductive success and survival. Despite these influences, few studies have integrated the analysis of nest location, behavior, and physiological status. In this study, we analyzed 20 black-tailed gulls (Larus crassirostris) nesting in the center of a colony within a protected area (Central Group, CG) and five gulls on the periphery outside the protected area, where human disturbance is frequent (Peripheral Group, PG). Using GPS movement trajectories and physiological indicators, we found that although clutch sizes were similar between the CG and PG, the PG exhibited shorter foraging trip durations, maximum distances from the nest, and a lower daily frequency of foraging trips. Antioxidant capacity did not differ between the groups; however, oxidation levels were lower in the PG. These behavioral and physiological differences associated with nest location may partly result from the incubation period influenced by human activity. The PG individuals remained in the peripheral group for at least 2 years (some for over 15 years), with all reproductive attempts failing, suggesting consistently low reproductive success. However, reduced foraging activity and lower oxidative stress levels reflect an energy-saving strategy that may mitigate the costs of repeated breeding failures. These findings suggest a potential life-history trade-off, in which individuals prioritize survival over reproductive success. This highlights how external disturbances and nest location can shape energy allocation strategies within a colony’s peripheral-central distribution.